Implementasi Pembelajaran Jarak Jauh Berbasis Literasi Digital Di Era Disrupsi - Niniek Misniati (Prosiding Temu Ilmiah Nasional Guru, 2022)
Distance learning has begun to be applied with sophisticated and fast media. Information sources can be accessed on various digital-based platforms. Improving the quality of human resources in managing information needs to be optimized. Digital literacy is one of the alternatives in improving the quality of human resources to be able to obtain, receive and use information in a healthy, wise, intelligent, careful, precise, and law-abiding manner according to its use. This article aims to describe students in using digital media as a source of literacy in learning and problem solving in everyday life. The method used in writing this scientific paper uses literature study. The results of the writing of this scientific paper produce the following formulation; the need for strengthening digital literacy-based learning for students from elementary school level, increasing the implementation of learning in the formal, informal and non-formal sectors based on digital literacy, increasing facilities and infrastructure such as computers, equitable distribution of the internet network and increasing resource capacity people through digital literacy trainings, and strengthening awareness of personal data protection and digital security in the era of disruption.